Spinal Accessory Nerve to Suprascapular Nerve Neurotization for Brachial Plexus Injury: A Retrospective Study - Seti Aji Hadinoto; Raditya Ramadhan (Surgery Department, Faculty of Medicine Universitas Sriwijaya, 2025)
Introduction: Brachial plexus injuries (BPIs) often lead to significant functional impairment of the upper extremity, particularly affecting shoulder abduction and external rotation. Spinal accessory nerve (SAN) to suprascapular nerve (SSN) neurotization is a surgical technique employed to restore shoulder function in these patients. This study aimed to evaluate the outcomes of this procedure in a series of patients with BPI. Methods: A retrospective observational case series study was conducted, including patients who underwent SAN to SSN neurotization for BPI at a single institution between January 2019 and December 2021. Patient demographics, injury characteristics, surgical details, and functional outcomes were collected from medical records. Functional outcomes were assessed using the Disabilities of the Arm, Shoulder, and Hand (DASH) score preoperatively and at the final follow-up. Results: A total of 8 patients were included in the study. The mean age was 25.7 years (range, 12-39 years), with a majority being male (55.6%). The most common cause of BPI was motor vehicle accidents (90%). The mean DASH score improved significantly from 72.5 preoperatively to 37.5 postoperatively (p<0.05). Conclusion: SAN to SSN neurotization appears to be a safe and effective technique for improving shoulder function in patients with BPI. This study demonstrated significant improvements in DASH scores following the procedure. However, further research with larger sample sizes and longer follow-up periods is needed to confirm these findings and evaluate the long-term outcomes of this technique.